Pathological evidence of infectious laryngotracheitis among layer birds in Kerala - S.S. Devi; Nisha Natarajan; K. Krithiga (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A carcass of four month old Gramasree layer bird from the district of was presented to the Dept. of Veterinary Pathology, College of Veterinary and Animal Sciences, Mannuthy for necropsy examination. Ten birds were reported to be dead with symptoms of conjunctivitis, respiratory distress and expectoration of blood stained mucus. A layer bird of nine months of age was also brought from Thrissur district showing similar symptoms. On necropsy, the tracheal mucosa was found to be severely congested with the lumen containing blood clots. The lungs were edematous, moderately hemorrhagic and congested. Histopathological examinations of the tracheal and lung tissues were carried out. There was appreciable infiltration of lymphocytes in the mucosa and submucosa associated with formation of syncytia by mucosal epithelial cells. The sloughed mucosal epithelial cells were seen within the tracheal lumen and high magnification of the epitheIial cells revealed the presence of intranuclear inclusion bodies. Lung revealed lesions of bronchointerstitial pneumonia along with hyaline membrane formation within the bronchioles. Bright red intra nuclear inclusion bodies were also demonstrated by special stains like Lendrum and Page Green.